Alzheimer's Disease: Background, Current and Future Treatments - Evelyn Chou (University Library System, University of Pittsburgh, 2014)
Alzheimer's disease is a currently incurable neurodegenerative disorder, and its treatment has posed a big challenge. Proposed causes of Alzheimer's disease include the cholinergic, amyloid and tau hypothesis. Current therapeutic treatments have been aimed at dealing with neurotransmitter imbalance. These include cholinesterase inhibitors and N-methyl D-aspartate receptor antagonists. However, current therapeutics have been unable to halt its progression. The future of Alzheimer's disease treatment thus appears to lie with prevention rather than cure. In this article, current therapeutics are discussed, and from there, the future of Alzheimer's disease treatment.